2014
DOI: 10.7150/ijms.8170
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Newcastle Disease Virus AF2240 Strain on Human Peripheral Blood Mononuclear Cells

Abstract: Immunotherapy has raised the attention of many scientists because it hold promise to be an attractive therapeutic strategy to treat a number of disorders. In this study, the immunomodulatory effects of low titers of Newcastle disease virus (NDV) AF2240 on human peripheral blood mononuclear cells (PBMC) were analyzed. We evaluated cytokine secretion and PBMC activation by cell proliferation assay, immunophenotyping and enzyme linked immunosorbent assay. The proliferation of the human PBMC was measured to be 28.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Only a recombinant version of the virus expressing interleukin (IL)-2 enhanced the concentration of IFN-γ in supernatant, when compared to control groups (21). Recently, employing a genotype VIII velogenic strain (AF2240) over human PBMC, it was demonstrated the capacity of this strain to stimulate IFN-γ production (17). Here, we found that PBMC (except from donor 4) respond to rNDV-P05 and LPS with an upregulation in IFN-γ secretion.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Only a recombinant version of the virus expressing interleukin (IL)-2 enhanced the concentration of IFN-γ in supernatant, when compared to control groups (21). Recently, employing a genotype VIII velogenic strain (AF2240) over human PBMC, it was demonstrated the capacity of this strain to stimulate IFN-γ production (17). Here, we found that PBMC (except from donor 4) respond to rNDV-P05 and LPS with an upregulation in IFN-γ secretion.…”
Section: Discussionsupporting
confidence: 50%
“…An increase at mRNA level was also observed. Our results highlight that although rNDV-P05 is recombinantly attenuated, it triggers a similar effect when compared with a velogenic strain (17), without needing the expression of foreign cytokines, such as IL-2 (21). The upregulation in IFN-γ induced by rNDV on human PBMC could be beneficial in vivo, due to IFN-γ is involved in activating anticancer immunity (T cells, NK cells and DCs), in inhibiting the activity of immune-suppressive cells (regulatory T cells and myeloid-derived suppressor cells), as well as in the conversion of tumor-associated macrophages (58,59).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previously it has been reported that these cytokines play an important role in innate/acquired immune responses and tumor suppression 34 as IFN-γ and IL-2 have the ability to activate immune cells including macrophages, NK cells and CTLs which have well known cancer cell killing capabilities. 35,36 The increased level of IFN-γ and IL-2 indicates that D. stramonium fraction-10 might be stimulating anticancer immune responses mediated through human lymphocytes. Taken together, present research explored the in vitro immunostimulatory potential of bioactive fraction-10 from D. stramonium that boosts the immune cells and enhances their anticancer abilities against human lung and breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches based on the immuno-detection of halogen derivatives are very important procedures used for the detection of the replicational activity of cells, and serve as an important tool for the description of cellular proliferation and cell cycle by microscopy or flow cytometry as well, e.g., [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. They also enabled researchers to collect a new data about the organization of replication.…”
Section: Halogenated Analogs Of Nucleosides As a Tool For The Resementioning
confidence: 99%